EIGENVALUE SENSITIVITY APPROACH WITH GENERATOR REDISPATCH MECHANISM BASED ON UNIT COMMITMENT FOR DAMPING RATIO ENHANCEMENT OF POWER SYSTEM - Adjie Kurniya, Mahardhika
The implementation of a large-scale electrical power system is usually carried out because the availability of primary energy is not always located near the load center, so that the generated electrical energy needs to be sent through a transmission or distribution lines. In addition, a large-scale electrical power system can also increase reliability of the power supplied to the loads. But the larger the electrical system, the higher probability of disturbance occurred at any time. One of the disturbances is a small signal stability problem. The main cause of small signal problem is a low value of power system damping in the low frequency mode. It can cause oscillations in the generator’s rotor. Even, the problem will be more serious when the transmission lines are quite long. Therefore, the right solution to overcome this kind of disturbance is increase the damping value of the power system by rearranging the output of the active power generator (redispatch generator). Modification in generator’s dispatch can change the value of the damping ratio by utilizing the nonlinearity properties of electrical power system. In other words, generator redispatch will change the equilibrium point of the operating system. A linear stability analysis of the new equilibrium point will produce a mode with a new value of the frequency and new value of the damping ratio. Therefore, this thesis study will describe the approach of eigenvalue sensitivity’s change with generator redispatch mechanism to increase the damping ratio value of power system. But there is a development to the mechanism. Generator redispatch will consider the technical restriction and economic dispatch operation of each generator (unit commitment). At the end, the most optimal redispatch value to increase power system’s damping ratio with its generator redispatch pair will be obtained. The development of generator redispatch mechanism is also designed to be realistic for actual operation of electrical power system.